DAMPAK DARI PEMIKIRAN PEMUDI TENTANG MASA DEPAN DI DESA MEKAR MULYA, KECAMATAN PENARIK, KABUPATEN MUKOMUKO, PROVINSI BENGKULU - Rahmah, Nisa Fadillah; Matnur Ritonga (Jurnal Cakrawala Ilmiah, 2023)
This study describes the impact of high school dropout adolescents Madrasah Aliyah and its implications for personality formation efforts with the main problem of impact of dropping out of school adolescents on personality formation, discusses aspects of coaching for high school dropouts / madrasah aliyah in Kampiri village, Pamana district and implications for efforts to shape the personality of adolescents with high school dropouts / madrash aliyah in the village of Mekar mulya, Penarik sub-district, Wajo district. This problem is deeply rooted and difficult to solve and there is chaos in the community. Therefore, the authors want to know and research further about the impact of adolescents dropping out of high school levels of high school / madrasah aliyah and how aspects of development and implications and efforts in shaping adolescent personality. Answering these problems, the author uses research methods including descriptive qualitative research types, namely by describing, analyzing, the research approach used by researchers, namely the educational educational approach, psychological approach, and sociological approach with data collection methods by means of observation, interviews or interviews, study. documentation and library reseach. The data analysis method used is data reduction, data display (data presentation), conclusion drawing (data verification) combined with inductive and comparative analysis. The results of the research on the impact of teenagers dropping out of school at the high school / madrasah aliyah level on the formation of adolescent personality, namely unemployment, juvenile delinquency and poverty and aspects of coaching teenagers who drop out of school, namely Package C, parent motivation, operational assistance, socialization, operational funding assistance and skills development. Implications for efforts to shape the personality of teenagers who drop out of school at high school / madrasah aliyah levels in kampiri village, pammana sub-district, wajo district with the package C program and operational funds can increase the standard of living independently, and increase knowledge and reduce low economic burdens apart from Package C people's motivation parents and socialization foster enthusiasm for adolescents and better understand the nature of education accompanied by skill development so that unique and valuable works are created.